The New Typography - Tschichold, Jan (University of California Press, 2020)
Since its initial publication in Berlin in 1928, Jan Tschichold's The New Typography has been recognized as the definitive treatise on book and graphic design in the machine age. First published in English in 1995, with an excellent introduction by Robin Kinross, this new edition includes a foreword by Rich Hendel, who considers current thinking about Tschichold's life and work.
Keywords: Printing.; HISTORY / Europe / General.; ART / General; Printing